2018
DOI: 10.5455/jice.20170909091946
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of Annona senegalensis (Annonaceae) and Hallea ledermannii (Rubiacaceae) effects on glycemia in rats

Abstract: Aim: In order to promote African traditional pharmacopoeia, studies have been undertaken to evaluate the effects of aqueous extracts of Annona senegalensis (Annonaceae) (EAAs) and Hallea ledermannii (Rubiaceae) (EAHl) in white rats of Wistar strain. Methods: A phytochemical screening and a toxicological study according to the Organisation for Economic Co-operation and Development guidelines 423 were carried out. Pharmacological effects on blood glucose were evaluated. The different treatments were performed or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 9 publications
3
10
1
Order By: Relevance
“…No change was noted in bood glucose concentration. These results are similar to those of Nanti et al (2018) who noted that A. senegalensis root bark extract, at the oral single doses of 50, 200, and 300 mg/kg b.w., does not significantly alter blood glucose values 180 min after the treatement. However, it should be noted that the study design was different, the present study repeated administration in mice while that of Nanti et al (2018) was single-dose in rats.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…No change was noted in bood glucose concentration. These results are similar to those of Nanti et al (2018) who noted that A. senegalensis root bark extract, at the oral single doses of 50, 200, and 300 mg/kg b.w., does not significantly alter blood glucose values 180 min after the treatement. However, it should be noted that the study design was different, the present study repeated administration in mice while that of Nanti et al (2018) was single-dose in rats.…”
Section: Discussionsupporting
confidence: 91%
“…Interestingly, the decrease in food intake is correlated with a reduction in weight gain upon exposure to aqueous extract of root wood of A. senegalensis. Such results was not observed by Nanti et al (2018) in rat. These authors showed that single oral doses of aqueous extract of A. senegalensis root barks (550, 1,750, and 3,000 mg/kg b.w.)…”
Section: Discussionmentioning
confidence: 57%
See 3 more Smart Citations